Given, $\hat{i},$ $\hat{j}$ and $\hat{k}$ are unit vectors along x, y and z-axis respectively. Then,

\[\hat{i}.(\hat{j}×\hat{k})=\hat{i}.(-\hat{i}) \;\;\; [\because \hat{k}×\hat{j}=-\hat{i}]\] \[=-1 \;\;\; [\because\hat{i}.\hat{i}=1]\]

Given, $\hat{i},$ $\hat{j}$ and $\hat{k}$ are unit vectors along x, y and z-axis respectively. Then,

\[\hat{i}.(\hat{j}×\hat{k})=\hat{i}.(-\hat{i}) \;\;\; [\because \hat{k}×\hat{j}=-\hat{i}]\] \[=-1 \;\;\; [\because\hat{i}.\hat{i}=1]\]

We use cookies to improve your experience on our website